A Critique on the Book History of Iranian Studies in Russia - Abbas Panahi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Given that the book The History of Iranian Studies in Russia is one of the most recent works in the field of Iranian studies in Russia, the author was expected to critique the achievements of Russian Iranologists with an analytical approach; especially for the fact that, during the communist era, the Russians attached special importance to Iranian studies in line with the plans and policies of the ruling Soviet party. Because in the Soviet period, Iranian studies were based on the course of historical one-line theory and the proof of historical determinism. These works had a great impact on the intellectual, political, and social atmosphere of Iran in recent decades. As a result, the critique of the Russians' record in this field could have opened new perspectives in the field of Iranian studies (Iranology), while the book under review provides a brief and hasty record of the trend of Iranology in the three-hundred-year history of this science in Russia. One of the most important reasons for the dispersion of the book’s contents was to choose a general title for the present study. So, the indicators studied by the author cover a wide range of topics and contents in the field of Iranian studies in Russia. The indicators studied in the present book should be included in the scope of encyclopedia research. The present article tries to critique and analyze the topics and indicators of the present book by the method of content analysis and scientific critique.